2021
DOI: 10.3389/fphar.2021.795002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reimbursement Practices on the Pharmaceutical Market for Off-Patent Medicines in Slovakia

Abstract: Background: The aim of this study was to investigate the impact of selected legislative initiatives and their implementation for off-patent medicinal products in Slovakia compared with the rest of the Visegrád Group (V4 countries).Methods: We analyzed the development of applications for the reimbursement of generic and biosimilar drugs. Particular emphasis was placed on a) the availability and penetration of biosimilars from 2006 to 2020 in Slovakia, b) a comparative analysis of biosimilars in V4 countries bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The literature search yielded 1,037 records, of which 971 were excluded following screening. Of the 66 full-text articles that were assessed for eligibility, seven articles were included ( Value-based pricing, 2011 ; Puig-Junoy, 2012 ; Hollis and Grootendorst, 2017 ; Granlund and Bergman, 2018 ; Tesar et al, 2021 ; Medaxes, 2022 ; Moradpour et al, 2023 ). In addition, one relevant report from a consultancy agency was identified in the grey literature ( Invent, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 1,037 records, of which 971 were excluded following screening. Of the 66 full-text articles that were assessed for eligibility, seven articles were included ( Value-based pricing, 2011 ; Puig-Junoy, 2012 ; Hollis and Grootendorst, 2017 ; Granlund and Bergman, 2018 ; Tesar et al, 2021 ; Medaxes, 2022 ; Moradpour et al, 2023 ). In addition, one relevant report from a consultancy agency was identified in the grey literature ( Invent, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The variations in reimbursement and national policy are discussed as the main reason [25]. Recent data revealed that sales of biosimilars increased in 2020 in Slovakia, Hungary, and the Czech Republic and that they were higher than what was found for Poland [26].…”
Section: Discussionmentioning
confidence: 98%
“…They found that the sales of generic drugs in Poland fell from 40.4% in 2015 to 35.0% in 2020, from 26.2 to 22.1% in Hungary, and from 29.6 to 20.4% in Czechia. [ 45 ] Simoens analyzed the Polish generic market and concluded that Poland needs to consider moving away from competition by discount to competition by price [ 46 ].…”
Section: Discussionmentioning
confidence: 99%